Safety, pharmacokinetics, and antitumor response of depatuxizumab mafodotin as monotherapy or in combination with temozolomide in patients with glioblastoma. Issue 6 (25th October 2017) - Gan, Hui K; Reardon, David A; Lassman, Andrew B; Merrell, Ryan; van den Bent, Martin; Butowski, Nicholas; Lwin, Zarnie; Wheeler, Helen; Fichtel, Lisa; Scott, Andrew M; Gomez, Erica J; Fischer, JuDee; et al.
Abstract: Background: We recently reported an acceptable safety and pharmacokinetic profile of depatuxizumab mafodotin (depatux-m), formerly called ABT-414, plus radiation and temozolomide in newly diagnosed glioblastoma (arm A). The purpose of this study was to evaluate the safety and pharmacokinetics of depatux-m, either in combination with temozolomide in newly diagnosed or recurrent glioblastoma (arm B) or as monotherapy in recurrent glioblastoma (arm C). Methods: In this multicenter phase I dose escalation study, patients received depatux-m (0.5–1.5 mg/kg in arm B, 1.25 mg/kg in arm C) every 2 weeks by intravenous infusion. Maximum tolerated dose (MTD), recommended phase II dose (RP2D), and preliminary efficacy were also determined. Results: Thirty-eight patients were enrolled as of March 1, 2016. The most frequent toxicities were ocular, occurring in 35/38 (92%) patients. Keratitis was the most common grade 3 adverse event observed in 6/38 (16%) patients; thrombocytopenia was the most common grade 4 event seen in 5/38 (13%) patients. The MTD was set at 1.5 mg/kg in arm B and was not reached in arm C. RP2D was declared as 1.25 mg/kg for both arms. Depatux-m demonstrated a linear pharmacokinetic profile. In recurrent glioblastoma patients, the progression-free survival (PFS) rate at 6 months was 30.8% and the median overall survival was 10.7 months. Best Response Assessment in Neuro-Oncology responses were 1 complete and 2 partial responses. Conclusion: Depatux-m alone or in combination with temozolomide demonstrated an acceptable safety and pharmacokinetic profile in glioblastoma. Further studies are currently under way to evaluate its efficacy in newly diagnosed (NCT02573324) and recurrent glioblastoma (NCT02343406).